Metodyka budżetowania przedsięwzięć gospodarczych - wybrane metody - Mietlewski, Zygmunt (Methodology of Budgeting of Economic Enterprises - Chosen Methods, 2005)
Three author's methods are presented in this work, according to the author these methods improve process of budgeting of economic enterprises. The first method is called by the author the golden key of the division of the profit and the second is called method of the economic matrix of information links (EMPI).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 292-296